The interaction between learning style preferences and learning style practices among students of a vocational college in the Mekong Delta - Nguyễn, Xuân Thắm (Đại học Cần Thơ, 2011)
This research aimed at exploring cognitive learning styles preferred by students in the two different academic major fields in learning English as a foreign language. This paper also reported on a comparison of students’ learning style preferences with their learning style practices.